2022
DOI: 10.1007/978-3-030-97546-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning Techniques on a Novel Hierarchical Surgical Tool Dataset

Abstract: A new hierarchically organised dataset for artificial intelligence and machine learning research is presented, focusing on intelligent management of surgical tools. In addition to 360 surgical tool classes, we create a four level hierarchical structure for our dataset defined by 2 specialities, 12 packs and 35 sets. We employ different convolutional neural network training strategies to evaluate image classification and retrieval performance on this dataset, including the utilisation of prior information in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Owing to their capability of extracting image features at different levels of hierarchy, convolutional neural networks (CNNs) Table 3 Machine learning methods key findings, prominent advantages, and disadvantages are crucial to image processing tasks [28]. One of the strengths of this model is that it is very useful for applications that require real-time tracking; thereby, it can be used for surgical tool detection during operations [29]. Spatial transformer networks (STNs) combine with convolutional neural networks to make it possible to adjust spatial data.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to their capability of extracting image features at different levels of hierarchy, convolutional neural networks (CNNs) Table 3 Machine learning methods key findings, prominent advantages, and disadvantages are crucial to image processing tasks [28]. One of the strengths of this model is that it is very useful for applications that require real-time tracking; thereby, it can be used for surgical tool detection during operations [29]. Spatial transformer networks (STNs) combine with convolutional neural networks to make it possible to adjust spatial data.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…The authors in [29] developed a novel hierarchically organized dataset for research emphasizing intelligent surgical equipment management. A four-level hierarchical framework and 360 separate surgical instrument categories were applied to the dataset.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, all the datasets surveyed in our paper have a flat structure. Given that fact that surgery is organised along specialities (Table 7), and each speciality has separate underlying categories, a hierarchical classification of surgical tools in the datasets provided for machine learning research has been shown to be extremely valuable (Rodrigues et al, 2022(Rodrigues et al, , 2021a.…”
Section: Dataset Volume Variety and Qualitymentioning
confidence: 99%